Using Kahoot! Application in the Daily Evaluation of Arabic Lesson: Experimental Studies at Islamic Senior High School in Indonesia | Istikhd?m Kahoot! F? Al-Taqw?m Al-Yaum? li-M?dah Al-Lughah Al- - Muhammad Infithar Al Ahqaf; Khaled Eslayeh; Mustafa Farouq Abdul-Aleem Mahmoud; Saiul Anah; Usfiyatur Rusuly (Universitas Islam Negeri Palangka Raya, 2022)
The lack of technology to make practical Arabic learning evaluation is a concerning problem for researchers. The purpose of the study is to test the effectiveness of Kahoot! in the daily evaluation of Arabic lessons for students at Islamic Senior High School 1 Tapin in Indonesia. This study uses field research with a quantitative approach. The desain used is quasi-experimental with the pretest-posttest control group. The population of this study is students in eleventh grade, with a total of 190. The sample is taken using purposive sampling, and 58 students are divided into experimental and control group. The data collection method is a test. The data analysis to answer the research hypothesis is the Mann-Whitney U test. The results show that the posttest average score from the experimental group was 83.62 and the control group was 73.79, which means that the experimental group's Arabic learning outcome is higher than the control group's. On the other hand, the results of the Mann-Whitney U test show Asymp. Sig. (2-tailed) 0.013 <0.05 means that the hypothesis Ha is accepted, and H0 is rejected. It can be concluded that using Kahoot! in the daily evaluation of Arabic learning effectively enhances student learning outcomes.